PROGNOSTIC BIOMARKERS IN CONGENITAL HEART DISEASE - Azizova, N.A. (World of Medicine and Biology, 2025)
This study aimed to assess the diagnostic significance of N-terminal pro-B-type natriuretic peptide in detecting and evaluating disease severity in infants less than one year of age with congenital heart disease. Results showed, that N-terminal pro-B-type natriuretic peptide levels in critically ill infants with congenital heart anomalies were approximately 10 times higher than in healthy infants (p
Keywords: congenital heart anomalies; NT-proBNP; lactate; mortality risk indicator; infants